Exploring Users' Experience of the Web - Brown, Barry A. T.; Sellen, Abigail (First Monday, 2001)
While browsing the Web is a widespread everyday activity there is a shortage of detailed understanding of how users organise their Web usage. In this paper we present results from a qualitative in-depth interview study of how users browse the Web and combine browsing with their other activities. The data are used to explore three particular problems which users have with browsing the Web. Firstly, users have problems managing their favourites, and in particular accessing their favourites through a hierarchical menu. Second, users have problems with combining information across different Web sites - what we call the “meta-task” problem. Third, users have concerns with security and privacy, although these concerns seem to change as users become more experienced with shopping on the Web. We discuss three concepts which address these problems: “home page favourites”, “Web clipping” and the “Web card”. These concepts are attempts at incremental improvements to the Web without affecting the Web's essential simplicity.